Guanidine‐Derived Polymeric Nanoinhibitors Target the Lysosomal V‐ATPase and Activate AMPK Pathway to Ameliorate Liver Lipid Accumulation - Yunfei Zhao; Ke Hu; Fangliang Wang; Lulu Zhao; Yu Su; Jun Chen; Gang Zou; Liming Yang; Li Wei; Mengjiao Deng; Yunyu He; Ping Wang; et al. (Advanced Science)
Abstract Current research efforts in polymer and nanotechnology applications are primarily focused on cargo delivery to enhance the therapeutic index, with limited attention being paid to self‐molecularly targeted nanoparticles, which may also exhibit significant therapeutic potential. Long‐term and anomalous lipid accumulation in the liver is a highly relevant factor contributing to liver diseases. However, the development of the reliable medications and their pharmacological mechanisms remain insufficient. Herein, a polyguanide nanoinhibitors (PGNI) depot is constructed by copolymerizing biguanide derivatives in different proportions onto prepolymers. The nanoinhibitors for their ability to ameliorate lipid accumulation in vitro and in vivo is screened, and subsequently demonstrated that covalently polymeric guanidine chains exhibit superior efficacy in ameliorating hepatic lipid accumulation via heterogeneous mechanisms compared to small‐molecule guanidine. It is found that PGNIs stabilize guanidine metabolism in the liver, preferably for biosafety. More importantly, PGNI is ingested and localized in hepatocyte lysosomes and is locked to interact with vesicular adenosine triphosphatase (V‐ATPase) on lysosomes, leading to the inhibition of V‐ATPase and lysosomal acidification, thereby activating the AMPK pathway, reducing fatty acid synthesis, and enhancing lipolysis and fatty acid oxidation. These results imply that polymer‐formed nanoparticles can serve as targeted inhibitors, offering a novel approach for therapeutic applications.